2011
DOI: 10.1002/lary.22370
|View full text |Cite
|
Sign up to set email alerts
|

Speech processing: From peripheral to hemispheric asymmetry of the auditory system

Abstract: Language processing from the cochlea to auditory association cortices shows side-dependent specificities with an apparent left hemispheric dominance. The aim of this article was to propose to nonspeech specialists a didactic review of two complementary theories about hemispheric asymmetry in speech processing. Starting from anatomico-physiological and clinical observations of auditory asymmetry and interhemispheric connections, this review then exposes behavioral (dichotic listening paradigm) as well as functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 69 publications
3
40
0
1
Order By: Relevance
“…From the asymmetrical hemispheric functioning of speech processing and its left dominance (see Lazard et al 2012a for a review), a right ear advantage was sought to answer the question "does implanting the right ear in adults provide better speech understanding?" The analyses did not show any effect of side on speech performance, even at later ages when the right ear advantage for speech may increase (Martin & Jerger 2005).…”
Section: Everyday Clinical Data Cannot Explain Asymmetrical Results Imentioning
confidence: 99%
See 1 more Smart Citation
“…From the asymmetrical hemispheric functioning of speech processing and its left dominance (see Lazard et al 2012a for a review), a right ear advantage was sought to answer the question "does implanting the right ear in adults provide better speech understanding?" The analyses did not show any effect of side on speech performance, even at later ages when the right ear advantage for speech may increase (Martin & Jerger 2005).…”
Section: Everyday Clinical Data Cannot Explain Asymmetrical Results Imentioning
confidence: 99%
“…So far, in the case of left implantation, it is not possible to say whether left auditory input uses direct ipsilateral projections from the cochlear nucleus, or whether decussation taking place at higher relays becomes predominant, or both. Similarly, the role played by the efferent medial olivocochlear efferent system (see Lazard et al 2012a for a review) is unknown in the case of deafness and compensatory reorganization. However, our hypothesis of a nondominant ear in adult CI recipients may not be true in children.…”
Section: Everyday Clinical Data Cannot Explain Asymmetrical Results Imentioning
confidence: 99%
“…In addition, linear reasoning, numeric and arithmetic skills are often lateralized to the left side of the brain [111]. For language, lateralization is variable: grammar and vocabulary are lateralized to the left hemisphere of the brain, prosodic language functions, like intonation and accentuation, are controlled by the right hemisphere [112][113][114] stated that speech at an early phonological level is processed bilaterally, but higher-level processing is supported by the left hemisphere. Furthermore, face recognition is thought to be mainly lateralized to the right side [115][116][117] suggested that the left hemisphere controls more routine processes or rehearsed processing, the right hemisphere is more involved in novel situations.…”
Section: Cerebral Asymmetrymentioning
confidence: 98%
“…Segregation of the speech signal means that non-primary auditory areas are divided into two distinct temporal integration windows: the first, faster system has a higher temporal resolution and is located in the left side whereas the second, slower system has a higher spectral resolution and is located in the right hemisphere. The underlying theory behind this explanation for auditory cortex asymmetry is called the spectral / temporal resolution tradeoff theory [114,186]. The other theory is the so called asymmetric sampling in time theory [184].…”
Section: Functional Asymmetrymentioning
confidence: 99%
See 1 more Smart Citation